Effect of Packaging Materials on the Shelf Life of Frozen Fish Fingers - K.P., Antony; T.K., Srinivasa Gopal; R., Thankamma; P.V., Prabhu (Fishery Technology, 2025)
A commercially available lean fish, Sciaena aneus, was used for making battered and breaded fish fingers. The fish fingers were packed in flexible film pouches of SOJ,L Low density polyetheylne (LOPE), 62.5JJ. Low density polyethylene- High density polyethylene (LO/HOPE), 20J.1 High molecular weight high density polyethylene (HM-HOPE) and lOOJJ. Low density polyethylene-Nylon-Primacore (LOPE/NY /PC), heat sealed and stored at -20"C and storage quality evaluation was conducted in comparison to the control sample which was kept without packaging. Control samples were discarded in 4 weeks time due to rancidity development, tough texture aand colour changes. The samples packed in LO/ HOPE and LOPE/NY /PC remained in satisfactory condition up to 28 and 32 weeks, respectively, whereas LOPE and HM-HOPE packed samples remained in satisfactory condition only for 20 weeks.